Beyond Proficiency: A Mixed-Methods Study of Student Readiness, Learning Awareness, and Comprehension in an EMI-Based Sociolinguistics Course - Samsidar; Muh. Safar Nur (Seltics Journal: Scope of English Language Teaching Literature and Linguistics, 2025)
This study examines the challenges encountered by English as a Foreign Language (EFL) learners in an Indonesian university implementing English as a Medium of Instruction (EMI). Using a mixed-methods approach, data were collected from 70 undergraduate students enrolled in a Sociolinguistics course taught fully in English. Questionnaire results indicate moderate levels of learning readiness and metacognitive awareness, alongside notable differences in content comprehension between students from urban and rural backgrounds. Follow-up interviews and classroom observations contextualized these disparities, highlighting issues such as cognitive overload, gaps in prior English exposure, and varied use of metacognitive strategies. The findings suggest that readiness for EMI involves more than language proficiency; it reflects students’ learning habits, background preparation, and ability to regulate their learning. Practical implications include the need for targeted academic support, scaffolded instructional materials, and metacognitive strategy training to foster more equitable and effective EMI learning environments.